Isolasi Bakteri Salmonella sp dari Feses Sapi Aceh di Pusat Pembibitan, Aceh Besar - Cut Iusma Muzadin; Teuku Reza Ferasyi; Fakhrurrazi Fakhrurrazi (JURNAL ILMIAH MAHASISWA VETERINER, 2018)
This research was aimed to isolate Salmonella sp bacteria from cattle faeces of Aceh in the Center of Breeding, Aceh Besar. A total of 10 cattle taken faeces for sample. Then isolation of bacteria Salmonella sp was using Carter method isolation of Salmonella sp was conductes using inoculate faeces of performed cattle after taken using swab steril on the media Salenit Cystine Broth (SCB). Furthermore, the sample were planted on selective media of Salmonella Shigella Agar (SSA) and observed colony morphology. Next a microscopic observation with Gram staining. Then a was conducted suspected colony as bacterial Salmonella sp was tested by Biochemical test (Indol, MR-VP, SIM, Simmons Citrate, TSIA) and sugar test, which consists of (glucose, sucrose, lactose and manitol). The result of this research was analysed descriptively. The result of a total of 10 samples, can be isolated positive Salmonella sp on 2 samples.Keywords : Aceh cattle, Salmonella sp